Kangaroo Method: continuing education strategies for its implementation and execution - Nietsche, Elisabeta Albertina; Papa, Mariana Mileski; Terra, Larice Gonçalves; Reisdorfer, Ariele Priebe; Ramos, Tierle Kosloski; Antunes, Andrei Pompeu (Revista Cuidarte, 2019)
Introduction: To understand the context in which the kangaroo method is implemented based on the actions of Continuing Healthcare Education. Materials and Methods: A qualitative exploratory study was conducted with twelve professionals of the healthcare team. The data was collected through a semi-structured interview and later analyzed to validate its content. Results: Three categories of analysis were created: kangaroo method: conceptions and understandings; continuing education: teaching-learning strategies; and kangaroo method and teamwork: limitations and possibilities. Discussion: Educational actions were provided to neonatal ICU professionals before implementing the kangaroo method. However, the following issues were identified in the day-to-day implementation: low adherence of the multidisciplinary team in the execution of the kangaroo method; work overload; difficulty remembering instructions to place the newborn in the kangaroo position; lack of guidance given to relatives; and resistance of mothers to put it into practice. Conclusions: It was observed that the institution was concerned to provide educational actions to the neonatal ICU professionals before implementing the kangaroo method. However, it is necessary to constantly generate discussions on the subject to improve the work carried out by the healthcare team.Como citar este artigo: Nietsche EA, Papa MM, Terra LG, Reisdorfer AP, Ramos TK, Antunes AP. Método Canguru: estratégias de Educação Permanente para sua implementação e execução. Rev Cuid. 2020; 11(1): e897. http://dx.doi.org/10.15649/cuidarte.897
Keywords: Kangaroo-Mother Care Method; Education, Continuing; Patient Care Team; Health Personnel